Effect of kangaroo mother care in low-birth-weight babies in reference to breastfeeding in NICU at a tertiary care centre - An observational study - Kalita, Dulal; Sarma, Sumana (Asian Journal of Medical Sciences, 2024)
Background: Kangaroo mother care (KMC) is described by the WHO as early, ongoing, and prolonged skin-to-skin contact between a mother and her preterm infants. Aims and Objectives: (1) The aim of the study was to study the effect of KMC in growth of newborn and (2) to study the effect of KMC in prevention of hypothermia, apnea, and requirement of prolonged hospital stay. Materials and Methods: In this prospective, hospital based, observational study, 241 neonates who were hospitalized to the neonatal intensive care unit in Gauhati Medical College and Hospital, Guwahati between April 2023 and March 2024 were assessed. Every potential mother was trained for KMC and given exclusive breastfeeds, and contrasted with a control/(conventional method of care) group of mothers. Results: The KMC babies had better breastfeeding rates as compared to the control group (76% vs. 53.8%). The weight gain (14.9±4.7 vs. 10.5±4.1 g/day), increase in length (0.97±0.67 vs. 0.69±0.63 cm/week), chest circumference (0.73±0.35 vs. 0.49±0.19 G/week), and head circumference (0.74±0.52 vs. 0.50±0.31 g/week), was also better in the KMC group. The incidence of apnea and hypothermia was significantly less in the KMC group, and the duration of stay in hospital was less in the KMC group than the control group (10±5 vs. 16±8 days). Conclusions: KMC improves breastfeeding rates, improves growth, reduces morbidities, and decreases duration of hospital stay.